The commitment of educational counselors in Irbid governorate to the standards of the American Association for Counsellors - Mayas, Mohammad Mahmoud; Al-Shaqran, Hanan Ibrahim (Journal of Educational and Psychological Sciences, 2023)
The study aims to identify the degree of the commitment of educational counselors in Irbid governorate to the standards of the American Association for Counsellors. The sample of the study consisted of (212) male and female Counselors which were chosen by the method available in the directorates of Irbid Governorate. The measure of the extent to which educational counselors use the standards and ethics of the counseling profession based on the standards of the American Association of Educational Counselors were used. The results indicated that the degree to which the members of the study sample of educational counselors in Irbid governorate practice the scale of the educational counselors' use of the standards and ethics of the counseling profession based on the standards of the American Association of Counselors came at the intermediate level. The results also showed - there are statistically significant differences between the arithmetic averages of the use of educational counselors in Irbid Governorate for the standards and ethics of the counseling profession based on the standards of the American Association of Counselors due to the gender variable in favor of females, and the absence of statistically significant differences due to the variable of school level, academic qualification and years of experience.
Keywords: American Association of Counselors Standards; Educational Advisors